Perlindungan Hak Asasi Manusia Bagi Perempuan pada Kasus Kekerasan dalam Rumah Tangga di Indonesia - Siti Wulandari; Nailal Hana; Elvina Nabila S (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Human rights are inherent from the moment a person is born into the world. The purpose of Human Rights is as a means of protection for someone because no one knows that human nature can change at any time. In Indonesia itself, human rights are highly respected as one of the mandates of the 1945 Constitution of the Republic of Indonesia. Domestic Violence (KDRT) often makes women victims, this is because women are physically inferior to men. . Cases like this need to be given more attention to protect women who are victims of domestic violence, because human rights violations can trigger physical and mental health problems for the victims. The purpose of this writing is to determine the protection provided to victims of domestic violence. Data analysis used qualitative research methods with a normative juridical approach, namely an approach based on the main legal material by examining theories, legal principles and laws. Domestic Violence is currently regulated in Indonesian legislation, such as: The Criminal Code, Law No. 23 of 2004 concerning the Elimination of Domestic Violence. Forms of direct legal protection through existing institutions such as: Integrated Service Centers and Assistance Agencies.